Comparison of different methods to overexpress large genes - Aline Lisie Ramos; Fernanda Soares Niemann; Adriana Silva Santos Duarte; Karla Priscila Ferro; Irene Santos; Carolina Louzão Bigarella; Antonio Filareto; Sara Teresinha Olalla Saad (Journal of Biological Research, 2018)
Gain-of-function of very large transgene constructs can lead to genetic perturbations, providing researchers with the alternative of a powerful tool to identify pathway components which remain undetected when using traditional loss-of-function analysis. To promote longer-term expression, various systems for transgene integration have been developed, however large cDNA sequences are often difficult to clone into size-limited expression vectors. We attempted to overexpress ARHGAP21, a 5.874 kb gene, using different methodologies as plasmid, lentiviral and Sleeping Beauty (SB) transposon based gene transfer. Using lentiviral based transduction; an enormous amount of lentiviral supernatant was produced to obtain a satisfactory titration after double ultracentrifugation. However, U937 transduced cells showed only 50% of gene expression increase, which vanished after 5 days. SB transposon system application to overexpress ARHGAP21 was a complete success. Nucleofecting SB-based vector plus SB100x transposase vector resulted in an expressive increase of gene and protein expression. Furthermore, the overexpression was maintained even after freezing and thawing processes. In conclusion, our work shows that the SB transposon system is the best choice for those seeking a stable and high gene expression. Once the overexpression is achieved, freezing cells and using them for a long time becomes possible.